ANALYSIS OF MACROECONOMIC FACTORS AFFECTING SHARE PRICE OF PT. BANK MANDIRI Tbk - Camalia Zahra (President University Press, 2017)
This research is aims to investigate the affect of selected macroeconomic factors toward share price volatility either partially and simultaneously by shrinking the scope of research in commercial bank, specifically in PT. Bank Mandiri Tbk., Indonesia. Multiple regression analysis is applied in this research to construct a quantitative model that will show the research objective. The result indicates that only inflation rate which has no significant affect. Instead, three macroeconomic factors comprise of BI rate, USD exchange rate, and unemployment rate are significantly affecting share price of Bank Mandiri. The regression model show that these four factors affecting share price simultaneously with the value of adjusted R square 0.547. It indicates that 54.7% share price of Bank Mandiri could be explained by these factors while the remaining of 45.3% might be explained by other factors outside the research.